Budidaya Tanaman Sayuran Di Kelompok Karang Taruna Tani Pasir Mas Dengan Pemanfaatan Teknologi Sonic Bloom - Harahap, Fitra Syawal; Hilwa, Walida; Fauzi Ahmad , Syawaluddin (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Vertical farming technique is a method used for community settlements that have narrow land optimally. This technique will arrange plants in tiers from top to bottom with various types of plants. The purpose of this community service (PKM) is to help improve the understanding and ability of the Karang Taruna Tani Villa Pasir Mas group partners to grow vegetables so that they can meet their daily vegetable needs and reduce living costs by utilizing existing land using sonic bloom technology. The community service partners trained in this service are 25 partners aged 30-50 years. The methods used are socialization, training and mentoring. The results achieved are an increase in Partners' understanding of sonic bloom technology to 80%, Partner knowledge 98% and Partners' desire to cultivate vegetables with sonic bloom by 100%.